Development of venture philanthropy in the conditions of the hybrid war: areas of improvement of accounting support - G.Yu. Khomenko (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article specifies that the combination of venture philanthropy and social investment principles leads to a high level of engagement and a long-term approach to creating the social effect of invested capital and the efforts of venture investors and recipient enterprises. The presence of military conflicts on the territory of Ukraine, as well as the fact of annexation of the Crimea make our country economically unstable and unattractive for potential investors. Therefore, there is a problem of finding new alternative sources of financing for the socio-economic development of economic entities, as well as certain socially disadvantaged groups of the population, which need social support from the state and indifferent investors. The nature and role of venture philanthropy in funding charitable activities of NGOs were identified during the research. Its main purpose is to assist non-profit organizations in the promotion of innovative ideas of a social nature, as well as to ensure the sustainable development of such organizations and their social projects, which are of great benefit to society and have a long-term social impact. In general, the use of venture philanthropy is an interesting approach to charity, combining best investment practices with nonprofit values to achieve the greatest social impact. This kind of charity has been found to mean attracting financial resources, time, reputation, personal and professional contacts, but at the same time it provides a much broader impact in addressing major social issues. Taking into account the identified specificity of financing social programs on the basis of venture philanthropy, the directions of improvement of accounting support of management of such financing were formed in order to further evaluate the effectiveness of venture capital participation in social projects.